The Role of Kindergartens in the Development of Islamic Values and National Identity in the Light of the Vision of Saudi Arabia (2030) - Samara, Hatouf (Dirasat: Educational Sciences, 2021)
This study aims to reveal the role of kindergartens in developing Islamic values and national identity in light of the Kingdom’s vision (2030) from the viewpoint of kindergarten teachers, and whether there viewpoint differ according to their specialization and years of experience. The study sample consisted of (55) kindergarten teachers in a city Hail, during the year 2019/2020. They were chosen randomly, and the descriptive approach was followed by applying a questionnaire to the study sample. The results showed that the role of kindergarten in developing Islamic values from the point of view of teachers was very high at the following dimensions: the role of the curriculum, and the role of the teacher, but a high degree for the role of kindergarten activities, and it showed that the role of kindergarten in developing the national identity from the point of view of teachers was very high on the three dimensions. It also showed that there are no statistically significant differences between the responses of kindergarten teachers in its two dimensions: Islamic values and national identity due to specialization and years of experience.